Experiments of sweet potato technology in South Hungary - Szarvas, Adrienn; Monostori, Tamás (Acta Agraria Debreceniensis, 2017)
The overall objectives of our research program are to examine and to develop the possibilities of use and to expand the national production technology of sweet potato. In 2016, we have set up production technology experiments in many regions, from which we report the results of the experimental field in Deszk here. In our field experiments we obtained results of planting material production, planting and nutrition optimization of sweet potato. Rating the effects of different nutrition doses, between the averages of treatment we didn't experience any significant differencies. On hard soil we set up experimental plots with or without ridges. Based on the result of the harvest the production technology without ridges proved to be more effective. The transplants originating from cuttings from shoots or from tubers did not show significant differences, but it does matter how many tons of sweet potato tubers we harvest per hectare.